Impact of Bariatric Surgery on Patients from Goiás, Brazil, Using the BAROS Method: A Preliminary Study - Ribeiro,Emmeline Flor (2015)
Introduction: As obesity is currently a major public health problem, bariatric surgery has been widely indicated due to the difficulties involved in the clinical management of obese adults. Objectives: Assess the quality-of-life (QOL) of patients who had undergone Roux-en-Y Gastric Bypass (RYGB) in the State of Goiás, Brazil, where as yet no studies have been published on the QOL of patients who underwent bariatric surgery. Methods: A retrospective study, using the Bariatric Analysis and Reporting Outcome System (BAROS), was carried out in Goiânia and Rio Verde, Goiás, Brazil, with 50 over 18-year-old patients of both genders, who had undergone RYGB and had at least three months of postoperative time. Results: Before RYGB, 48% of the individuals were classified as morbidly obese. Average weight and body mass index (BMI) of the 50 patients interviewed were 119.37±18.44 kg and 43.54±5.33 kg/m², respectively. By contrast, after the RYGB these parameters decreased significantly to 78.01±11.06 kg and 28.46±3.61 kg/m², respectively, mainly from the 3rd to 85th month of postoperative time (p < 0.0001). As well as that, 78% reported having presented preoperative comorbidities, especially hypertension (44%), rheumatism (34%), dyslipidemia (24%) and diabetes (20%). However, after surgery, the resolution rates were 77, 24, 100 and 100%, respectively, for these same clinical conditions. In terms of QOL, some patients reported feeling better (8%) or much better (92%) after RYGB. The outcome of the BAROS method for those patients was classified as fair (2%), good (8%), very good (24%) and excellent (66%). Conclusions: Preliminary results indicated that RYGB could be a successful surgical procedure to promote satisfactory and sustained reduction in the body measurements of morbidly obese patients from Goiás, Brazil. Furthermore, the final BAROS score showed improvements in associated comorbidity and also in the QOL of these patients.